Ketergantungan Pada Validasi Sosial Melalui Like, Comment, Followers Di Media Sosial : Literature Review - Faza Ammarul Haq; Amirah (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
The development of social media has fundamentally changed how individuals interact and seek social validation. Features such as likes, comments, and followers have become measurable indicators of recognition that can affect self-esteem and psychological well-being. Objective: This systematic literature review aims to examine dependency on social validation through likes, comments, and followers on social media, analyzing its impact on mental health and psychological well-being. Methods: Article collection was conducted through three electronic databases: Google Scholar, Garuda, and PubMed, with criteria for original studies published in the last 10 years (2015-2025) and available in Indonesian language. Results: The review shows that dependency on social media validation is associated with various psychological impacts including anxiety, depression, decreased self-esteem, FOMO (Fear of Missing Out), and mental health disorders. Factors influencing this dependency include self-esteem, personality traits (particularly narcissism), age (adolescents being more vulnerable), intensity of use, and motives for social media use. Conclusion: A comprehensive risk management approach is needed to address the negative impacts of social validation dependency, including preventive strategies through digital literacy education and curative interventions through counseling and cognitive-behavioral therapy. Digital literacy programs, mental health support systems, and platform design changes are recommended to promote healthier social media use patterns.